Numerical simulation of fault characteristics for refrigeration systems with liquid line receivers. (November 2020) - Behfar, Alireza; Yuill, David
Abstract: Refrigeration systems can experience operating faults that negatively impact their performance, such as reducing their ability to maintain the temperature setpoint, increasing energy consumption, or reducing the life of the equipment. To better understand the impacts on the physical operating characteristics of a system, a numerical model can be used. However, fully physics-based models require significant computational effort and detailed system information that is typically unavailable; whereas data-driven models require a prohibitively large amount of test data. In this paper a gray-box model is described, using a semi-empirical approach from the literature. It combines into a complete cycle the models for each component: compressor, heat exchangers, pipelines, expansion valve, and liquid line receiver. A set of 35 test data from laboratory experiments on a commercial walk-in freezer was used for training and validating the model. The liquid line receiver was found to provide particular challenges for charge estimation, but the overall model performs quite well and is able to predict the effects of faults on most operating variables with reasonable accuracy.